2018
DOI: 10.1007/s10120-018-00910-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative wait time on survival in patients with clinical stage II/III gastric cancer

Abstract: Background Preoperative wait time is affected by various factors, and a certain time is needed before surgery. There is a concern that cancer treatment delay can lead to poor survival. The present study aimed to evaluate the impact of preoperative wait time on survival in patients with clinical stage (cStage) II/III gastric cancer. Methods The study included patients with cStage II/III primary gastric cancer undergoing surgery between 2002 and 2012. Preoperative wait time was defined as the time from endoscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Previous studies reported than a half-year wait time for surgery was not independently associated with the survival of patients with clinical stage I gastric cancer, 13 and a preoperative wait time up to 90 days did not affect survival in patients with clinical stage II/III gastric cancer. 14 The results in this study were consistent with previous studies. However, delayed gastrectomy is not recommended because of the preoperative waiting timerelated psychological distress and displeasure.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies reported than a half-year wait time for surgery was not independently associated with the survival of patients with clinical stage I gastric cancer, 13 and a preoperative wait time up to 90 days did not affect survival in patients with clinical stage II/III gastric cancer. 14 The results in this study were consistent with previous studies. However, delayed gastrectomy is not recommended because of the preoperative waiting timerelated psychological distress and displeasure.…”
Section: Discussionsupporting
confidence: 93%
“…However, as previously described, a waiting time beyond more than 90 days before surgery would not affect overall survival in patients with clinical stages I, II and III. [13][14][15] Previous studies have proven that the birth season may affect the incidence of tumors, and furthermore, tumors diagnosed in winter may affect the prognosis as well. 16,17 However, one study reported that the diagnosis season did not affect the prognosis of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…When we conduct preoperative interventions, there is a concern about tumor progression, particularly in patients with advanced cancer. However, preoperative wait time up to 90 days has been reported not to affect survival even in cStage / gastric cancer patients [30]. Hence, obese patients might have the bene ts of fewer complications by preoperative exercise.…”
Section: Discussionmentioning
confidence: 99%
“…These facts cannot be overseen, also, cancer is a bigger problem than COVID-19 from patient's perspective. Table 1 summarises various studies addressing the impact of time to treatment initiation or delaying surgeries on cancer survival [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Keeping these concerns in mind, some guidelines have recommended a possible triage ( Table 2) to offer surgeries, even during the course of an active pandemic, for certain precarious malignancies who are known to have rapid progression.…”
Section: Cancer Surgery In Covid-19 Outbreakmentioning
confidence: 99%